Pollution prevention and restoration in the Golden Horn of Istanbul - (:unkn) unknown (IWA PUBLISHING, 1998)
The pollution in the Golden Horn is one of the most important environmental problems of Istanbul. Alluvium carried by Alibey and Kagithane creeks, and domestic and industrial wastewater discharges are the major sources of the pollution. In the upstream, a part of 3 to 4 km long is almost completely filed with debris and organic solids. There is a high anaerobic activity in the sediment resulting in a heavy odor problem. Sea traffic is impossible since the depth of water is less than 10 cm at this part. A restoration feasibility project has been carried out for pollution prevention and evaluation of the restoration alternatives. For this purpose, first, characteristics of water quality and bottom sediment were determined. Second, pollution prevention measures and the alternatives for the dredging and disposal of the bottom sediment were evaluated. Istanbul Metropolitan Municipality has already started the dredging work by early 1997, and has completed the diversion of all domestic and industrial wastewater discharges out of the Golden Horn. This paper summarizes the studies for determining current status, evaluating the restoration alternatives, and also the progress of the on-going dredging work. (C) 1998 IAWQ. Published by Elsevier Science Ltd.
Keywords: dredging; environmental restoration; Golden Horn; heavy metals; sediment; water quality